Hemodialysis associated dysautonomia; Effect of optimization of dialysis and nutrition: A prospective study - Sheashaa, Hussein; Wafa, Ehab; Sabry, Alaa; Aly, Magdy; Khalil, Abdalla; Tantawy, Abde El-Haleem; Sobh, Mohamed (African Journal of Nephrology, 2023)
Background: Autonomic neuropathy is common among hemodialysis patients, even if they are asymptomatic. The aim of this study is to assess the effect of optimization of patients' dialysis and nutrition on the presence of autonomic dysfunction in these patients guided by sympathetic skin response (SSR) test. Methods: Fifteen patients on maintenance hemodialysis (12 males and 3 females) their age ranged from 24 to 67 years, most of them were on bicarbonate dialysis were included in our study. Initially, the patients were assessed clinically and by laboratory investigations and their dialysis was assessed by studying their urea kinetic modeling. Their nutrition was assessed by laboratory parameters and by calculating the normalized protein catabolic rate (nPCR). Their autonomic functions were assessed by clinical examination, hand grip and SSR test. Dialysis dose was readjusted to achieve a target kt/v value of 1.3/session thrice weekly. Also, their nutrition was reviewed to achieve nPCR of 1.2 gm/kg/day and caloric intake of 30-40 KCal/kg/day through diet manipulation and support. They were reassessed after 3 months. Results: Analysis of the data showed a statistically significant improvement of the observed subclinical autonomic neuropathy evidenced by a significant change in the hand grip (p = 0.044), and a high statistically significant improvement in the sympathetic skin response test parameters (both amplitude and latency) (p=0.001) after optimization of both hemodialysis and nutrition status. Conclusion: Improving dialysis and patients nutrition by using urea kinetic modeling is valuable in improving their autonomic functions as assessed by SSR test.